2019
DOI: 10.1101/807255
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ability of Bicarbonate Supplementation to Sensitize Selected Methicillin-ResistantStaphylococcus aureus(MRSA) Strains to β-Lactam Antibiotics in anEx VivoSimulated Endocardial Vegetation Model

Abstract: Word Count: 3963 25 2 ABSTRACT 26 Supplementation of standard growth media (cation-adjusted Mueller-Hinton Broth 27[CAMHB]) with bicarbonate (NaHCO 3 ) significantly increases β-lactam susceptibility of selected 28 MRSA strains ("NaHCO 3 -responsive"). This "sensitization" phenomenon translated to enhanced 29 β-lactam efficacy in a rabbit model of endocarditis. The present study evaluated NaHCO 3 -30 mediated β-lactam MRSA sensitization using an ex vivo pharmacodynamic model, featuring 31 simulated endocardial… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Additional studies have shown that buffering with bicarbonate, the major anionic buffer in mammalian physiology, is a major contributor to the superior predictability of physiological media in vitro antibiotic susceptibility to in vivo efficacy [ 11 ]. For example, some strains of methicillin-resistant Staphylococcus aureus (MRSA) demonstrate a methicillin-susceptible phenotype in bicarbonate-buffered media, and such strains can be effectively treated in animal models of endocarditis with beta-lactam monotherapy [ 11 , 13 ]. Azithromycin efficacy against multiple gram-negative bacterial species (eg, Acinetobacter baumannii , Klebsiella pneumoniae ) depends on bicarbonate, and this activity translates to in vivo efficacy in murine infection models [ 14 , 15 ].…”
Section: Conventional Bacteriologic Media: An Obstacle To Our Completmentioning
confidence: 99%
“…Additional studies have shown that buffering with bicarbonate, the major anionic buffer in mammalian physiology, is a major contributor to the superior predictability of physiological media in vitro antibiotic susceptibility to in vivo efficacy [ 11 ]. For example, some strains of methicillin-resistant Staphylococcus aureus (MRSA) demonstrate a methicillin-susceptible phenotype in bicarbonate-buffered media, and such strains can be effectively treated in animal models of endocarditis with beta-lactam monotherapy [ 11 , 13 ]. Azithromycin efficacy against multiple gram-negative bacterial species (eg, Acinetobacter baumannii , Klebsiella pneumoniae ) depends on bicarbonate, and this activity translates to in vivo efficacy in murine infection models [ 14 , 15 ].…”
Section: Conventional Bacteriologic Media: An Obstacle To Our Completmentioning
confidence: 99%
“…Recently, we identified a novel MRSA AST phenotype, termed "NaHCO3-responsiveness", in which MRSA strains are highly susceptible in vitro to CFZ and OXA in media supplemented with NaHCO3 (7). Prototype MRSA strains with this in vitro phenotype were also highly susceptible to these same β-lactams in an ex vivo simulated endocarditis vegetation model, as well as in a rabbit model of infective endocarditis (7,10). In contrast, in vitro NaHCO3 non-responsive isolates were also resistant to CFZ and OXA under these same ex vivo and in vivo conditions.…”
mentioning
confidence: 99%